ISOLATED TORSION OF A TUBAL ECTOPIC PREGNANCY: MUST BE KEPT IN MIND - Mustafa DEMİR; Mert Ulas BARUT; Mehmet AĞAR; Sinan KARAGECİLİ; Orhan BİNİCİ; Murat BOZKURT; Bulent YILMAZ; Aytek Bulat ŞIK; Ayşe Ender YUMRU (Rojan GÜMÜŞ, 2017)
Isolated fallopian tube torsion without involvement of the ovary is a rare condition most frequently presenting during reproductive years. The majority of the diagnoses are made on the operating table. We describe a case of isolated tubal torsion, unique in that localized necrosis and inflammation from the torsion. Its common symptoms are lower abdominal pain, vomiting, and nausea. Because these symptoms are nonspecific, isolated torsion of a fallopian tube may be misdiagnosed, delaying treatment and the opportunity to preserve the tube. The ultrasound-assisted examination was useful, but the specific diagnosis was made after laparotomy and histopathology. Laparotomy and laparoscopy are important tools in the diagnosis and prognosis of isolated torsion of a fallopian tube, and can help to preserve the fertility of these patients.